2016
DOI: 10.1142/s1793292016500491
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt/Chromium Nanoparticles-Incorporated Carbon Nanofibers as Effective Nonprecious Catalyst for Methanol Electrooxidation in Alkaline Medium

Abstract: Cobalt-Chrome nanoparticles-incorporated carbon nano¯bers (CNFs) are proposed as an e®ec-tive nonprecious electrocatalyst for methanol oxidation in the alkaline media. The introduced nano¯bers were prepared by simple technique, electrospinning. Carbonization of as-spun mat composed of chromium acetate, cobalt acetate and poly(vinyl alcohol) (PVA) at high temperature (900 C) leads to production of the introduced nano¯bers. The physicochemical characteristics were investigated by X-ray di®ractometer (XRD), scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The formed gases reduced the salt and metal oxides to form pure Ni and Cr and/or their alloys rather than their oxides [2]. The formation of Ni and Cr can be defined by the following reactions [44,45]:Ni(CH 3 COO) 2 ·4H 2 O → 0.86Ni(CH 3 COO) 2 0.14 Ni(OH) 2 + 3.72 H 2 O + 0.28 CH 3 COOH…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formed gases reduced the salt and metal oxides to form pure Ni and Cr and/or their alloys rather than their oxides [2]. The formation of Ni and Cr can be defined by the following reactions [44,45]:Ni(CH 3 COO) 2 ·4H 2 O → 0.86Ni(CH 3 COO) 2 0.14 Ni(OH) 2 + 3.72 H 2 O + 0.28 CH 3 COOH…”
Section: Resultsmentioning
confidence: 99%
“…The nanofibrous morphology of the sintered electrospun NF mats was not affected by the high calcination temperature. This may be attributed to the polycondensation of the NiAc and CrAc with PVA [3,20,44,46]. Figure 1c,d shows the sintered NFs obtained after the abnormal calcination of electrospun NF mats composed of NiAc/CrAc/PVA.…”
Section: Resultsmentioning
confidence: 99%
“…The doped-Cd C NPs in the graphite shell prepared by Abdelkareem with the sol-gel method had enhanced catalytic activity for MOR, and its current density was 70 mA/ cm 2 , the initial potential was 600 mV (NHE), [118] which indicated that it was conducive to the MOR. In this study, [119] doped-Co Cr 7 C 3 nanorods inset with carbon nanofibers were used as a new low-cost and high-efficiency catalyst (using the sol-gel method). The material's morphology was studied and the result showed lattice fringes' distance was 0.221 nm, which was the intermediate value of Co and Cr 7 C 3 , semblable distributions of Co, Cr, and C were found, showing the stable orthogonal structure of CoCr 7 C 3 -CNFs [147] and the carbon coverage of Co and Cr 7 C 3 facilitated their catalytic activity for MOR.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…It is lower than the value measured under CoCr 7 C 3 -CNFs nanocomposite (65 mA/cm 2 ). Mohamed et al [119] modified CoÀ Cr NPs on carbon nanofibers. Compared with CoCr 7 C 3 -CNFs nano-composites, methanol oxidation reaction (+ 320 mV (Ag/AgCl)) was also detected a positive starting value.…”
Section: Other Transition Metal Catalystsmentioning
confidence: 99%
“…Electrochemical experiments including CV, CA and EIS were achieved by Potentiostat/ Galvanostat/ZRA Gamry instrument. The electrochemical studies were investigated according to the 3-electrode system as reported before 22,23 . The measurements were repeated to test the reproducibility of the results.…”
mentioning
confidence: 99%